2014
DOI: 10.3413/nukmed-0646-14-02
|View full text |Cite
|
Sign up to set email alerts
|

Expression of somatostatin receptor subtype 2 and subtype 5 in thyroid malignancies

Abstract: SSTR 5 was shown to be the main receptor subtype in the analysed differentiated or anaplastic thyroid malignancies, whereas SSTR 2 was found only in a small percentage. Deficient SSTR expression may indicate higher risk for persistent or recurrent disease after initial therapy. For this reason immunohistochemistry can be considered a prognostic marker which should be further validated in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…In this study, we have demonstrated that SSTR2A and SSTR5 are expressed in various degrees in a portion (66.0% and 37.5%, respectively) of MTCs. This is in concordance with other studies . SSTR2A and 5 staining was always combined membranous and cytoplasmic.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we have demonstrated that SSTR2A and SSTR5 are expressed in various degrees in a portion (66.0% and 37.5%, respectively) of MTCs. This is in concordance with other studies . SSTR2A and 5 staining was always combined membranous and cytoplasmic.…”
Section: Discussionsupporting
confidence: 93%
“…SST 2 was present in 43%–66% of medullary as well as in papillary and follicular thyroid carcinomas ( Papotti et al, 2001 ; Druckenthaner et al, 2007 ; Mussig et al, 2012; Pazaitou-Panayiotou et al, 2012 ; Atkinson et al, 2013 ; Woelfl et al, 2014 ; Herac et al, 2016 ). SST 2 was also detected in a high percentage (>70%) of pheochromocytomas and paragangliomas ( Fischer et al, 2008 ; Lupp et al, 2011 ; Saveanu et al, 2011 ; Elston et al, 2015 ) as well as in 33% of both functioning and nonfunctioning adrenocortical adenomas ( Unger et al, 2008 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…SSTRs are one class of receptors that could be targeted using NPs. These receptors are found either exposed on the surface of the cell or within the cell [9][10][11]. These cells are target cells for that ligand while cells which do not have such a receptor cannot be influenced directly by that ligand [12].…”
Section: Introductionmentioning
confidence: 99%